A networked self and human augmentics, artificial intelligence, sentience - Papacharissi, Zizi; Taylor and Francis (Boca Raton, FL : Routledge, an imprint of Taylor and Francis, 2018)
Every new technology invites its own sets of hopes and fears, and raises as many questions as it answers revolving around the same theme: Will technology fundamentally alter the essence of what it means to be human? This volume draws inspiration from the work of the many luminaries who approach augmented, alternative forms of intelligence and consciousness. Scholars contribute their thoughts on how human augmentic technologies and artificial or sentient forms of intelligence can be used to enable, reimagine, and reorganize how we understand our selves, how we conceive the meaning of "human", and how we define meaning in our lives.
chapter 1 Introduction / Zizi Papacharissi -- chapter 2 The Robot Dog Fetches for Whom? / Judith Donath -- chapter 3 Self in the Loop: Bits, Patterns, and Pathways in the Quantified Self / Natasha Dow Schüll -- chapter 4 Posthuman Futures: Connecting/Disconnecting the Networked (Medical) Self / Laura Forlano -- chapter 5 Other Things: AI, Robots, and Society / David J. Gunkel -- chapter 6 Taking Social Machines Beyond the Ideal Humanlike Other / Eleanor Sandry -- chapter 7 Beyond Extraordinary: Theorizing Artificial Intelligence and the Self in Daily Life / Andrea L. Guzman -- r Douglas Guilbeault Joel Finkelstein -- chapter 13 AI, the Persona, and Rights / Tamara Shepherd -- chapter 14 Untitled, No. 1 (Human Augmentics) / Steve Jones.
Keywords: TECHNOLOGY & ENGINEERING / Engineering (General); TECHNOLOGY & ENGINEERING / Reference; Artificial intelligence -- Psychological aspects; Assistive computer technology; Human-machine systems; Self